Africa's Soft Power Philosophies, Political Values, Foreign Policies and Cultural Exports - Tella, Oluwaseun (Global Africa, 2021)
This book investigates the ways in which soft power is used by African countries to help drive global influence. Selecting four of the countries most associated with soft power across the continent, this book delves into the currencies of soft power across the region: from South Africa's progressive constitution and expanding multinational corporations, to Nigeria's Nollywood film industry and Technical Aid Corps (TAC) scheme, Kenya's sport diplomacy, fashion and tourism industries, and finally Egypt's Pan-Arabism and its reputation as the cradle of civilisation. The book asks how soft power is wielded by these countries and what constraints and contradictions they encounter. Understandings of soft power have typically been driven by Western scholars, but throughout this book, Oluwaseun Tella aims to Africanise our understanding of soft power, drawing on prominent African philosophies, including Nigeria's Omolúwàbí, South Africa's Ubuntu, Kenya's Harambee, and Egypt's Pharaonism. This book will be of interest to researchers from across political science, international relations, cultural studies, foreign policy and African Studies.